Implicit memory reduced selectively for negative words with aging - Ladd, Sandra L.; Gabrieli, John D. E. (Frontiers in Aging Neuroscience, 2024)
Background: Disproportionally better memory for positive versus negative information (mnemonic positivity effect, MPE) in older versus younger adults has been reported on tests of explicit memory (direct, intentional) as measured by recall and recognition. The purpose of this investigation was to examine whether the MPE would be observed for implicit memory (indirect, unintentional) under conditions where, based on previous research using single words, it was expected that the MPE for explicit memory would be absent.